2023
DOI: 10.3389/fpubh.2023.1125125
|View full text |Cite
|
Sign up to set email alerts
|

Health needs and perception of health care quality among Asylum Seekers and Refugees in an Italian local health authority: A qualitative study

Abstract: BackgroundMigrants, Asylum Seekers and Refugees (ASRs) represent a vulnerable diversified population with increased risks of developing health problems, and in the hosting countries several barriers often hamper their access to the health services. Gathering information about ASRs’ experiences and perceptions of host country health care systems may contribute to improve the quality of health care provided. The aim of this study was to explore the health needs in their bio-psycho-social meaning, and the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Similarly, the findings of a study on refugees' perception of service quality in Italy revealed several obstacles, such as linguistic barriers, lack of cultural mediation, bureaucratic barriers, and lack of familiarity with the health care system. ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the findings of a study on refugees' perception of service quality in Italy revealed several obstacles, such as linguistic barriers, lack of cultural mediation, bureaucratic barriers, and lack of familiarity with the health care system. ( 16 ).…”
Section: Introductionmentioning
confidence: 99%